The Insidious Remnants of State Rules Respecting Capital Formation - Rutheford B. Campbell Jr. (Washington University Law Quarterly, 2000)
The purpose of this Article is to argue that Congress, notwithstanding the significant problems illuminated by public choice theory and interest group analysis, should complete the work it started with the National Securities Markets Improvement Act of 1996 by entirely preempting state control over capital formation. Only in this manner is it possible to reach the goal of a modern, fair, and efficient regulatory scheme for capital formation.
Keywords: Blue sky laws; Exclusive & amp; concurrent legislative powers; Capital market; Initial public offerings; Securities law; Working capital; National Securities Markets Improvement Act of 1996